2007
DOI: 10.1002/humu.20561
|View full text |Cite
|
Sign up to set email alerts
|

Molecular heterogeneity in fetal forms of type II lissencephaly

Abstract: Type II lissencephaly (type II LIS) is a group of autosomal recessive congenital muscular dystrophies (CMD) associated with defects in alpha-DG O-glycosylation, which comprises Walker-Warburg syndrome, Fukuyama cerebral and muscular dystrophy, or muscle-eye-brain disease. The most severe forms of these diseases often have a fetal presentation and lead to a pregnancy termination. We report here the first molecular study on fetal type II LIS in a series of 47 fetuses from 41 unrelated families. Sequencing of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…Cobblestone lissencephaly is characterized by a nodular brain surface, with a severely disorganized and unlayered cerebral and cerebellar cortex, and a disrupted pial layer. In addition to classical and cobblestone lissencephaly, there are three less common subtypes of the disorder, designated as X-linked lissencephaly with agenesis of the corpus callosum, lissencephaly with cerebellar hypoplasia, and microlissencephaly (Bouchet et al 2007;Verrotti et al 2010;Wynshaw-Boris et al 2010; Barkovich et al 2012;Huang et al 2012 (MIM 236670), POMPT1] and other α-dystroglycanopathies. In addition, there are many newly identified genes associated with various unclassified syndromes within the lissencephaly spectrum.…”
mentioning
confidence: 99%
“…Cobblestone lissencephaly is characterized by a nodular brain surface, with a severely disorganized and unlayered cerebral and cerebellar cortex, and a disrupted pial layer. In addition to classical and cobblestone lissencephaly, there are three less common subtypes of the disorder, designated as X-linked lissencephaly with agenesis of the corpus callosum, lissencephaly with cerebellar hypoplasia, and microlissencephaly (Bouchet et al 2007;Verrotti et al 2010;Wynshaw-Boris et al 2010; Barkovich et al 2012;Huang et al 2012 (MIM 236670), POMPT1] and other α-dystroglycanopathies. In addition, there are many newly identified genes associated with various unclassified syndromes within the lissencephaly spectrum.…”
mentioning
confidence: 99%
“…Prognosis critically depends on the presence of additional cerebral and extracranial malformations, which are observed in about 70-80% of the cases [Schrander-Stumpel and Fryns, 1998]. Important syndromal forms of congenital hydrocephalus include the autosomal recessive syndromal lissencephalies type 2 Walker-Warburg syndrome and Muscle-eye-brain disease with additional observation of a hypoplastic cerebellum and brainstem together with cobblestone lissencephaly and agenesis or hypoplasia of the corpus callosum as well as postnatal congenital muscular hypotonia, various eye abnormalities and global developmental delay, which in about half of the cases result from mutations in one of currently 6 genes associated with the O-glycosylation of ␣-dystroglycan [Bouchet et al, 2007]. The most frequent monogenic form of congenital hydrocephalus is due to hemizygous mutations in the L1CAM gene (about 7-15%) and clinically characterised by the distinct combination of a hydrocephalus due to stenosis of the aqueduct of Sylvius commonly in association with adducted thumbs (HSAS) [Tapanes-Castillo et al, 2010;Vos et al, 2010].…”
mentioning
confidence: 99%
“…Since this study, results from three other populations have been reported in which mutations in POMT1, POMT2, POMGNT1, LARGE, FKTN and FKRP were systematically screened. Each study analysed a defined clinical presentation and detected mutations in a total of 53%, 40% and 51% of CMD and two WWS patient cohorts respectively [9][10][11]. Taken together, these studies strongly implicate novel genes in the pathogenesis of the dystroglycanopathies.…”
Section: Genotype-phenotype Correlations: Additional Parametersmentioning
confidence: 97%
“…These studies have firmly established that the clinical spectrum associated with mutations in specific causative dystroglycanopathy genes is in fact far wider than originally appreciated. Hence, in the majority of cases the identity of the defective gene cannot be predicted from the clinical phenotype (Box 1) [9][10][11][12][45][46][47][48].…”
Section: Genotype-phenotype Correlations: Additional Parametersmentioning
confidence: 99%